The importance of entrepreneurship in education in Colombia media (2016)
The main factor for the development of a productive and competitive society is education. Equality right and improvement in quality of life have become a target for people who see in training a window for job creation and acquisition of resources. Education systems in developing countries focus on supporting and guiding business ideas and innovation of young people from basic education, having a special focus on the use of new technologies and scientific research. Entrepreneurship is defined as a way of thinking and acting oriented wealth creation. In Colombia entrepreneurship has become mandatory course in official institutions to guide young people towards this goal, the use or not of this depends on each of the young people and their own desire for development.